Isolation of a Xanthobacter sp. degrading dichloromethane and characterization of the gene involved in the degradation - Emanuelsson, Maria A. E. (2010)
A bacterial strain able to degrade dichloromethane (DCM) as the sole carbon source was isolated from a wastewater treatment plant receiving domestic and pharmaceutical effluent. 16S rDNA studies revealed the strain to be a Xanthobacter sp. (strain TM1). The new isolated strain when grown aerobically on DCM showed Luong type growth kinetics, with lmax of 0.094 h-1 and Sm of 1,435 mg l-1. Strain TM1 was able to degrade other aromatic and aliphatic halogenated compounds, such as halobenzoates, 2-chloroethanol and dichloroethane. The gene for DCM dehalogenase, which is the key enzyme in DCM degradation, was amplified through PCR reactions. Strain TM1 contains type A DCM dehalogenase (dcmAa), while no product could be obtained for type B dehalogense (dcmAb). The sequence was compared against 12 dcmAa from other DCM degrading strains and 98% or 99% similarity was observed with all other previously isolated DCM dehalogenase genes. This is the first time a Xanthobacter sp. is reported to degrade DCM.